2018
DOI: 10.1186/s12944-018-0854-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic profiling of extracellular vesicles derived from prostate and prostate cancer cell lines

Abstract: BackgroundExtracellular vesicles (EVs) are produced and secreted from most cells of the body and can be recovered in biological fluids. Although there has been extensive characterisation of the protein and nucleic acid component of EVs, their lipidome has received little attention and may represent a unique and untapped source of biomarkers for prostate cancer diagnosis and prognosis.MethodsEVs were isolated from non-tumourigenic (RWPE1), tumourigenic (NB26) and metastatic (PC-3) prostate cell lines. Lipids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 49 publications
6
125
0
Order By: Relevance
“…These differences in lipid composition could stem from the presence of lipoproteins in Lipo‐NPs, as triglycerides are associated with lipoproteins in the body 36. However, other studies have shown that cancer cell‐derived EVs contain high amounts of glycerolipids, making it difficult to draw any conclusions 37…”
Section: Resultsmentioning
confidence: 98%
“…These differences in lipid composition could stem from the presence of lipoproteins in Lipo‐NPs, as triglycerides are associated with lipoproteins in the body 36. However, other studies have shown that cancer cell‐derived EVs contain high amounts of glycerolipids, making it difficult to draw any conclusions 37…”
Section: Resultsmentioning
confidence: 98%
“…A study on prostate cancer has shown that the accumulation of cholesterol esters in prostate cancer cells is associated with tumor progression and metastasis. This was confirmed by studies, using synthetic exosomes carried out by the Lombardo Group, which showed that exosomal lipids can increase the tumor aggressiveness, metastatic progression and drug resistance of pancreatic cancer cells [31].…”
Section: Tumor Progressionmentioning
confidence: 68%
“…One potential application of TFAC utilizing ultrathin membranes as a microfluidic‐based technique would be isolation of EVs. Studies have indicated that not only the RNA content of these vesicles but also their protein varies by cell of origin as well as by the pathologic state of these cells . This differential cell state specific and cellular origin‐based content indicates that EVs could serve as biomarkers of disease.…”
Section: Discussionmentioning
confidence: 99%